Perkawinan yang Berkenan: Kajian Hermeneutik Kritik Historis Berdasarkan 1 Korintus 7:1-16 dan Implikasinya Bagi Jemaat - Sangian, Eiffel; Tewu, Peggy Sandra (Educatio Christi, 2024)
This article is about marriage and divorce. This letter was written by Paul to the church in Corinth. Paul emphasized the importance of maintaining the sanctity of marriage and avoiding fornication. He also offered a solution for married couples to stay away from each other by mutual consent for a while, in case of problems in their marriage. Paul reminds us that divorce is not a way out. The article entitled "Marriage Pleasing to God" teaches the attitude of love, respect, and appreciation in living a harmonious Christian family relationship but also the fear of God. And invite every individual, including congregations, married families to prioritize common interests. In the context of the congregation, by reflecting the message of "Marriage that is pleasing to God" in the practice of church and family life, we can create a more harmonious family relationship, oriented towards the ministry of love for the common good.